A right to a fair trial in Uganda's Judicature (Visual-Audio Link) Rules: embracing the challenges in the era of Covid-19. Issue 3 (2nd July 2020) - Nanima, Robert Doya
Abstract : The application of the Uganda Judicature (Visual-Audio Link) Rules does not contextualise the complete protection of an accused's right to a fair trial during emergencies. A contextualisation of the right to a fair trial in international law and under Uganda's domestic law is done. An evaluation of the application of the Visual-Audio Rules in the context of its objectives and circumstances follows. The contribution proposes an accused-centred approach in the application of the Visual-Audio Rules. A conclusion and recommendations follow.